2020
DOI: 10.4018/978-1-7998-2377-3.ch004
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CSR on B2B Relationships

Abstract: The chapter addresses how ethical actions deliver value through sustainable competitive advantage. Corporate social responsibility (CSR) has a proven role in developing audience trust that increases brand equity among target audiences, thus ensuring that the brand sustains its competitive advantage through improved profitability, increased social trust, and favorable reputation in the market. Not only do businesses have a social responsibility to the markets from which they earn revenues, but buyers expect eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…Prior studies found that CSR practice can enhance BE 40 , which in turn plays a regulatory role in promoting corporate brand performance and brand value 41 . A company's brand is formed from its ethical conduct, and this is an important factor in determining the value of corporate BE 42 .…”
Section: Research Hypothesismentioning
confidence: 99%
“…Prior studies found that CSR practice can enhance BE 40 , which in turn plays a regulatory role in promoting corporate brand performance and brand value 41 . A company's brand is formed from its ethical conduct, and this is an important factor in determining the value of corporate BE 42 .…”
Section: Research Hypothesismentioning
confidence: 99%